The summit - Korman, Gordon (New York : Scholastic, 2012)
Four climbers, making a final push to be the youngest people to reach the summit of Mount Everest, must deal with low supplies, extreme conditions, a storm, and possible sabotage by one of their companions.
6.4
3-6.
3-6
Keywords: Mountaineering -- Juvenile fiction; Adventure and adventurers -- Fiction; Mountaineering -- Fiction; Adventure fiction; Mountaineering -- Fiction; Everest, Mount (China and Nepal) -- Juvenile fiction; Everest, Mount (China and Nepal) -- Fiction; Mount Everest (China and Nepal) -- Fiction; Adventure fiction